Wayang KALENG DANCE AT THE DAYA SORA ETNIKA SANGGAR, BOGOR CITY IN THE FORM OF DANCE PRESENTATION - Alfira Hadiatiningrum; Deden Haerudin; Nursilah Nursilah (Universitas Pendidikan Indonesia, 2022)
The main problem in this research is how to dance wayang cans at the Daya Sora Ethnic Studio, Bogor City in the form of dance presentations. This study aims to determine and describe how the wayang dance is presented at the Daya Sora Ethnic Studio. This study uses a descriptive research methodology with a qualitative approach. Data collection techniques used are the results of observations, interviews, literature studies and document studies. By using data analysis, namely data reduction, data presentation, and drawing conclusions. The result of this research is that the wayang can dance is an art originating from the city of Bogor. Wayang Kaleng dance is a new type of dance creation which in its performance uses zinc as a substitute for gunungan and used cans as a medium for expressing puppets. This dance is like a puppet dance in general, but the form of presentation is packaged differently from its original form. The conclusion is that the creation of the canned wayang dance is the utilization of waste cans into useful items with a touch of creative art into a new type of puppet that can be played in various situations and various stories. The stories presented are very flexible, simple light stories, from stories for children to stories for teenagers, even parents, and anyone can create the desired story according to the theme and mission of the story to be conveyed, the function of wayang cans is more or less the same. Among them are entertainment, education, and social functions. The conclusion is that the creation of the canned wayang dance is the utilization of waste cans into useful items with a touch of creative art into a new type of puppet that can be played in various situations and various stories. The stories presented are very flexible, simple light stories, from stories for children to stories for teenagers, even parents, and anyone can create the desired story according to the theme and mission of the story to be conveyed, the function of wayang cans is more or less the same. Among them are entertainment, education, and social functions. The conclusion is that the creation of the canned wayang dance is the utilization of waste cans into useful items with a touch of creative art into a new type of puppet that can be played in various situations and various stories. The stories presented are very flexible, simple light stories, from stories for children to stories for teenagers, even parents, and anyone can create the desired story according to the theme and mission of the story to be conveyed, the function of wayang cans is more or less the same. Among them are entertainment, education, and social functions. The stories presented are very flexible, simple light stories, from stories for children to stories for teenagers, even parents, and anyone can create the desired story according to the theme and mission of the story to be conveyed, the function of wayang cans is more or less the same. Among them are entertainment, education, and social functions. The stories presented are very flexible, simple light stories, from stories for children to stories for teenagers, even parents, and anyone can create the desired story according to the theme and mission of the story to be conveyed, the function of wayang cans is more or less the same. Among them are entertainment, education, and social functions.